Evaluation of the effect of locoregional treatment on metabolic liver function in hepatocellular carcinoma using 18F-FDGal PET/CT - Mona Kjærbøl Kristiansen; Kirstine Petrea Bak-Fredslund; Stine Kramer; Gerda Elisabeth Villadsen; Michael Sørensen (EJNMMI Research)
Abstract Background The effect of different locoregional treatments for hepatocellular carcinoma (HCC) on metabolic liver function is largely unknown. This information is crucial, particularly for patients with cirrhosis. We applied [18F]-fluoro-2-deoxy-D-galactose (18F-FDGal) positron emission tomography (PET) to determine the contribution of large HCCs to total metabolic liver function and the changes in metabolic liver function post-treatment. Results We included 29 patients with HCC treated with resection (n = 8), radiofrequency ablation (RFA) (n = 8), transarterial chemoembolization (TACE) (n = 9), and selective internal radiation therapy (SIRT) (n = 4). In patients with HCCs > 3 cm, the liver’s total metabolic activity was significantly higher when including the metabolically active tumor areas compared to when the tumor was excluded (p = 0.0002). The median percent change in mean metabolic activity in the liver after locoregional treatment was 5.1% in patients without cirrhosis as compared to -6.0% in patients with cirrhosis (p = 0.05). The distribution of cirrhosis (n = 15 in total) among treatment groups was uneven. After treatment, seven of eight patients who underwent resection showed increased or stable mean metabolic liver function, while responses for those treated with RFA, TACE, or SIRT were mixed. Changes in mean metabolic liver function and liver volume did not correlate. Conclusions HCCs > 3 cm contributed substantially to the liver’s galactose metabolism, suggesting that this would also apply to other substrates used for measuring metabolic liver function. Changes in metabolic capacity following treatment depend on cirrhosis status and type of treatment. Changes in functional liver volume do not necessarily reflect total metabolic capacity. The study underlines the power of imaging-based quantification of metabolic liver function.